Ameliorative potentials of quercetin against cotinine-induced toxic effects on human spermatozoa - Dale Goss; Ibukun P. Oyeyipo; Bongekile T. Skosana; Bashir M. Ayad; Stefan S. du Plessis (Asian Pacific Journal of Reproduction, 2016)
Objectives: Cotinine, the principal metabolite of nicotine found in smokers' seminal plasma, has been shown to adversely affect sperm functionality while quercetin, a flavonoid with diverse properties is associated with several in vivo and in vitro health benefits. The aim of this study was to investigate the potential benefits of quercetin supplementation against damage caused by the by-products of tobacco smoke in human sperm cells. Methods: Washed human spermatozoa from 10 normozoospermic donors were treated with nutrient medium (control), quercetin (30 μmol/L) and cotinine (190 μg/mL, 300 ng/mL) with or without quercetin for 60 and 180 min incubation periods. Computer-aided sperm analysis was used to assess sperm motility while acrosome-reacted cells were identified under a fluorescent microscope using fluorescein isothiocyanate-labelled Pisum Sativum Agglutinin as a probe, viability was assessed by means of a dye exclusion staining technique (eosin/nigrosin) and oxidative stress by flow cytometry using dihydroethidium as a probe. Values were expressed as mean ± S.E.M. as compared by ANOVA. Results: Higher cotinine concentrations reduced the number of viable cells after 60 and 180 min of exposure while viability of cells was increased in the cotinine aliquots supplemented with quercetin after 180 min of exposure when compared with cotinine only treated group. Conclusion: This study indicates that the ameliorating ability of quercetin on cotinine-induced decline in sperm function is associated with increased number of viable cells.